Exploring the Prevalence of Psychological Symptoms among Healthcare Workers in Saudi Arabia: A Contemporary Analysis - Saqer Jarallah Alharthi,; Norah Mohammed Hazazi,; Mohammed Helil Alanezi,; Nawaf Mohammed Alhawtan,; Hanan Hamed Alenezi,; Eid Muqbil Lafi Alharbi,; Hamad Dafalh Alrakhimy,; Saud Mohammed Alharbi,; Otaibi Thawab Alharthi,; Raed Saad AL-Harthi,; Safar Bayn Alotaibi,; Thamer Almarzooqi,; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Healthcare workers (HCWs) play a crucial role in maintaining public health, particularly during crises such as the COVID-19 pandemic. The psychological toll on HCWs has been substantial, with increased prevalence of anxiety, depression, post-traumatic stress disorder (PTSD), and burnout. This paper explores the prevalence of psychological symptoms among HCWs in Saudi Arabia, analyzing factors contributing to mental health issues, coping mechanisms, and potential interventions. Using recent research, systematic reviews, and meta-analyses, the study provides a comprehensive overview of the psychological burden faced by HCWs in Saudi Arabia. The findings highlight the need for structured mental health support systems, policy reforms, and workplace interventions to mitigate the psychological impact on HCWs.